2019
DOI: 10.1113/ep087401
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of exercise‐induced changes in mRNA expression and technical considerations for qPCR analysis in human skeletal muscle

Abstract: New Findings What is the central question of this study?Are individual changes in exercise‐induced mRNA expression repeatable (i.e. representative of the true response to exercise rather than random error)? What is the main finding and its importance?Exercise‐induced changes in mRNA expression are not repeatable even under identical experimental conditions, thereby challenging the use of mRNA expression as a biomarker of adaptive potential and/or individual responsiveness to exercise. Abstract It remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Further, we recently found poor reproducibility for acute changes in skeletal muscle mRNA expression following identical exercise bouts in a similar population. 27 Because changes in mRNA expression following acute exercise are thought to represent the initiation of adaptive processes that contribute to chronic changes in aerobic capacity, 28 the lack of reproducibility in mRNA responses may partly explain the lack of reproducibility in observed VO 2 max responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we recently found poor reproducibility for acute changes in skeletal muscle mRNA expression following identical exercise bouts in a similar population. 27 Because changes in mRNA expression following acute exercise are thought to represent the initiation of adaptive processes that contribute to chronic changes in aerobic capacity, 28 the lack of reproducibility in mRNA responses may partly explain the lack of reproducibility in observed VO 2 max responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there have been wide differences in measured mRNA expression within muscle between trained and untrained subjects in response to exercise [149,150], suggesting that transcriptomics may hold promise as a "predictor" of training outcomes. More recently, however, authors have suggested that the association between increased mRNA expression and increased gene expression may not be as strong as once thought [151], and, indeed, may be due to technical error or random biological variation [152]; as a result, transcriptomics may not be as useful as proteomics within the personalised medicine approach to athlete preparation.…”
Section: The Integration Of Other "Omes"mentioning
confidence: 99%
“…This is consistent with previous research showing that not all individuals respond the same way to a standardised exercise dose [39][40][41] . This individual response could be due to genetic background, non-genetic biological and behavioral factors, day-to-day fluctuations, and technical or biological variability associated with the sampling of human skeletal muscle and the analysis of exercise-induced mRNA 42,43 .…”
Section: Compared 19mentioning
confidence: 99%